Analysis of Digital Transformation and the Future of Banking: Challenges and Opportunities in an Era of Technological Advancement - Nuryana, Ida (Universitas Islam Kadiri, 2024)
Abstract Digital transformation has had a significant impact on the banking industry, influencing the way banks operate and interact with customers. In the current era of technological advancement, banking faces new challenges and unlimited opportunities. This study aims to analyze digital transformation for the future of banking, focusing on the challenges and opportunities faced. The research method used is literature study and secondary data analysis. The research results show that digital transformation has changed the banking landscape in various ways. The main challenges faced by banks are data security and privacy, rapid technological developments, changes in consumer behavior, and increasingly fierce competition. To overcome this challenge, banks need to adapt quickly and develop innovative strategies. Overall, digital transformation brings challenges and opportunities for banking in an era of technological advances. Banks that are able to overcome these challenges and take advantage of existing opportunities will become leaders in the future banking industry. Keywords: Banking;Digital Transformation;Technologi.